Pemenuhan Hak Atas Makanan Bagi Warga Binaan Sebagai Hak Asasi Manusia di Lembaga Pemasyarakatan Kelas IIB Gunung Sugih Berdasarkan Peraturan Menteri Imigrasi dan Pemasyarakatan Nomor 1 Tahun 2025 - Erlina B.; Jennyza Febrianda (SENTRI: Jurnal Riset Ilmiah, 2026)
This study analyzes the fulfillment of the right to food for inmates as a human right in the Class IIB Gunung Sugih Correctional Institution based on the Regulation of the Minister of Immigration and Corrections Number 1 of 2025. The research method used is normative and empirical legal research. Through a legislative and conceptual approach and direct phenomena in the field. The results of the study indicate that although there is a strong constitutional guarantee for the provision of food for inmates based on the Regulation of the Minister of Immigration and Corrections Number 1 of 2025 concerning food standards for inmates, its implementation still faces gaps with field practices. The structural challenges identified include the problem of overcapacity of correctional institutions, disharmony in implementing regulations, limited human resources, and weak legal protection. This study recommends the need for regulatory harmonization, optimization of alternative sentencing, increasing the capacity of correctional officers, strengthening the monitoring system based on civil society participation and independent institutions to realize a just correctional system that respects human rights in accordance with the mandate of the constitution and international standards.